ARTPSY FUSION PROGRAM: UPAYA PENCEGAHAN RESIDIVISME PADA JUVENILE SEX OFFENDER SEBAGAI BENTUK RETROGRESI MORAL MELALUI TEATRIKAL WAYANG GOLEK - Yunita Putri Lestari; Sri Maslihah; Selfiyani Lestari; Febrian Kusnadi; Maitria Prada Yusuf; Syifa Fauziah; Candra Nugaraha Setiawan (Indonesian Psychological Research, 2024)
This research aims to overcome moral retrogression in juvenile sex offenders through the Artpsy Fusion Program intervention which uses Wayang Golek performances to insert culture-based moral values. This research uses a qualitative experiment approach with a pretest and posttest design. Data collection was carried out through in-depth interviews. The research participants consisted of six children who were children assisted by the Bandung Class II Special Child Development Institute (LPKA). The Artpsy Fusion Program intervention was carried out three times for three weeks. The research results show that the Artpsy Fusion Program is effective in improving moral reasoning in juvenile sex offenders. Content analysis showed there was a significant change in participants' moral reasoning after the intervention, with a shift from immature moral reasoning to more mature moral reasoning. Apart from that, by combining cultural aspects through Wayang Golek performances, it adds a valuable cultural dimension in efforts to improve the morale of young people who commit sexual crimes. Theoretical implications for moral retrogression in juvenile sex offenders and practical implications for intervention in LPKA are also discussed.